2020
DOI: 10.1038/s41467-020-18938-z
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of phase transitions and glass phase signatures in mixed cation halide perovskites

Abstract: Cation engineering provides a route to control the structure and properties of hybrid halide perovskites, which has resulted in the highest performance solar cells based on mixtures of Cs, methylammonium, and formamidinium. Here, we present a multi-technique experimental and theoretical study of structural phase transitions, structural phases and dipolar dynamics in the mixed methylammonium/dimethylammonium MA1-xDMAxPbBr3 hybrid perovskites (0 ≤ x ≤ 1). Our results demonstrate a significant suppression of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
108
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(136 citation statements)
references
References 74 publications
27
108
1
Order By: Relevance
“…Evolution of the CNC stretching and rocking modes of DMA [ 20,49 ] in terms of Raman shift (peak position) and linewidth (FWHM) as a function of temperature in the 44% DMA crystals. The dotted lines mark the phase‐transition temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Evolution of the CNC stretching and rocking modes of DMA [ 20,49 ] in terms of Raman shift (peak position) and linewidth (FWHM) as a function of temperature in the 44% DMA crystals. The dotted lines mark the phase‐transition temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…A similar trend was observed in DMA + -substituted MAPbBr 3 perovskites, for which the increasing of DMA + content eventually led to the suppression of the low-temperature phase transition. 28 Although the reasons for these changes in GA x-MA 1Àx PbI 3 are unknown, the fact that the e 0 peak cannot be seen in the GA 0.2 MA 0.8 PbI 3 composition in the temperature range studied suggests that guanidinium also causes an alteration in the low temperature phase transitions of MAPbI 3 .…”
mentioning
confidence: 89%
“…Single crystals of MAPbBr 3 (FAPbBr 3 ) with dimensions up to 10 mm were grown from mixtures containing PbBr 2 , acetonitrile, DMSO, HBr and a methanol solution of methylamine (formamidinium acetate) by antisolvent vapour-assisted crystallization using methyl acetate as the antisolvent (further details can be found in [11,24]).…”
Section: Materials and Synthesismentioning
confidence: 99%
“…X-ray diffraction data showed that MAPbBr 3 exhibits three phase transitions at 236, 153 and 144 K, which lead to a decrease of symmetry from cubic (Pm3m) to tetragonal I (I4/mcm), tetragonal II (P4/mmm) and orthorhombic (Pnma), respectively [22][23][24][25]. However, very recent X-ray diffraction data suggested that the intermediate phase, ascribed previously to the tetragonal phase II, has incommensurately modulated structure with the average space group Imma [26].…”
Section: Introductionmentioning
confidence: 99%